Implementasi Model Pembelajaran Kelompok, Sudut, Area, dan Sentra dalam Pembelajaran Anak Usia Dini - Yuniatari Yuniatari (UIN Mataram, 2020)
Education is a process of how to change a child's life for the better, independent andresponsible. The success of PAUD institution in implementing fun and play-orientedlearning depends on the extent to which the institution is able to design and implementeffective learning activities, so it requires learning management known as learningmodels. The purpose of examining the implementation of group learning model, corner,area and center in early childhood learning. This type of research is a literature study.The results showed that in implementing learning models in early childhood learning,both group learning model, corner learning model, area learning model, and centerlearning model require classroom management carried out by the teacher. In theassessment process, each learning model has the same assessment, that is, duringlearning activities, the teacher records everything that happens both to the developmentof students and the program of activities as a basis for assessment purposes.